Gender, emotions and fly-in fly-out work - Pini, Barbara; Mayes, Robyn (Australian Council of Social Service, 2013)
This paper explores the emotional life of fly-in fly-out (FIFO) workers and their families, through an analysis of more than 500 postings made on an online chat forum for mining families. Building on literature on fly-in fly-out workers and understandings of emotions as socially constructed, analysis shows how posters to the forum, typically women whose male partners are FIFO workers, construct gendered emotional identities for their partners (sometimes referred to as ‘Mr Miner’), and for themselves, as ‘mining women’, ‘mining widows’ or the ‘mining missus’. Inherent in the creation of gendered emotional subject positions is the process of women undertaking emotion work on and behalf of themselves, their male partners and their children. The findings demonstrate the overarching normative dimensions of women’s emotional self-transformations in the service of their mining partners’ careers and the attendant reproduction of everyday patriarchal relations in the private lives of mining families.